The Effect of Population, Human Development Index, Access to Proper Sanitation, and Access to Safe Drinking Water on Absolute Poverty in Jambi Province - Widiasari, Julas; Heriberta, Heriberta; Hardiani, Hardiani (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: This study aims to analyze the effect of population size, Human Development Index (HDI), access to improved sanitation, and access to safe drinking water on absolute poverty in Jambi Province. Background Problems: The relatively high level of poverty in Jambi Province is presumed to be influenced by demographic factors, the quality of human development, and limited access to basic services. Novelty: This research integrates population size, HDI, access to improved sanitation, and access to safe drinking water into a single panel data model at the regency/city level, which has not been comprehensively examined in the context of Jambi Province. Research Methods: This study uses secondary panel data of regencies/cities in Jambi Province for the period 2015–2024. The analytical method employed is panel data regression using the Random Effect Model (REM), supported by model selection tests and hypothesis testing. Finding/Results: The findings indicate that simultaneously, population size, HDI, access to improved sanitation, and access to safe drinking water significantly affect poverty. Partially, population size has no significant effect on poverty, while HDI has a negative and significant effect, improved sanitation has a negative and significant effect, and access to safe drinking water has a positive and significant effect. Conclusion: Improvements in human development quality and sanitation access can reduce poverty, while population size is not significant. The positive relationship of access to safe drinking water reflects development priorities in poorer areas, highlighting the need for integrated policies to improve human capital and ensure equitable access to basic infrastructure.